Tinjauan Bauran Pemasaran Sandal Tarumpah pada Toko Iskandar Toha 1946 Tasikmalaya - Kroma, Regina Putri Meisya; Ernawati; Puspatriani, Annisa Desty; Andi Tarlis (POLITEKNIK LP3I, 2024)
Marketing Mix is the core of a marketing system to influence demand for the products produced. The variables of the marketing mix are usually called the 4Ps, namely Product, Place, Promotion, and Place. By understanding and managing the marketing mix well, a company can increase its chances of achieving success in a competitive market. The aim of this final assignment is to determine the marketing mix used by Toko Iskandar Toha 1946 Tasikmalaya. The research method used is a qualitative method with a descriptive approach, describing the results of observations in the field with data collection methods using interviews, documentation, literature study and direct observation. The results of this research indicate that the marketing mix process for Tarumpah Sandals at the Iskandar Toha 1946 Tasikmalaya Store has been implementedquitewell.Keywords: Marketing, Marketing Mix